Agile Governance in the Digital Age: A Qualitative Study of Its Effectiveness and Implementation Challenges - Prasodjo, Tunggul (Manunggal Halim Jaya, 2025)
This research aims to explore the effectiveness and challenges of implementing agile governance in the digital age, focusing on its application within organizations undergoing digital transformation. The study utilizes a systematic literature review (SLR) methodology to synthesize and critically evaluate existing academic works on agile governance. By analyzing various studies published in the last decade, the research identifies key benefits, such as improved flexibility, decision-making speed, and alignment between operational activities and strategic goals. These advantages are particularly crucial for organizations striving to adapt to rapid technological advancements and shifting market dynamics. However, the study also highlights several challenges in adopting agile governance, including resistance to change, leadership gaps, and the need for a supportive organizational culture. The findings suggest that while agile governance can significantly enhance organizational agility, its successful implementation requires a comprehensive cultural transformation, the development of agile leadership competencies, and the strategic integration of digital tools. Additionally, the study calls for further research on the long-term impact of agile governance, its industry-specific applications, and the role of leadership in fostering agile environments. This research contributes to both theoretical development and managerial practice by offering insights into how agile governance can be effectively implemented in the digital era, ensuring organizations can navigate the complexities of digital transformation.